Peningkatan Pengetahuan dan Keterampilan tentang Pengelolaan dan Pelaporan Dana Desa di Desa Lubuk Enau Kecamatan Lembak - Rafika Sari; Harshi Romli; Muhammad Wadud; Siti Komariah Hildayanti (Universitas Muhammadiyah Semarang, 2022)
Lubuk Enau Village, Lembak District. This village was only inaugurated as a separate village in 2011 based on the regulation of the Regent of Muara Enim No. 25. In this village most of the people work as farmers. Based on the results of observations during KKN activities, Lubuk Enau Village is a village that has great potential and has rich natural resources. However, both the community and the city government of Lubuk Enau Village are less able to explore and manage economic potential even though this can be a source of income and allocation of funds. village for the welfare of the village community Community service activities carried out by lecturers and students of the Faculty of Economics, Indo Global Mandiri University by holding workshops with the village head and employees at the village head office in Lubuk Enau. The goal to be achieved is to provide increased knowledge and skills for village heads and their employees regarding Village Fund Management and Reporting